2020
DOI: 10.3390/app10207170
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Spherical Calcium Carbonate Nanoparticles Derived from Cockle Shells

Abstract: Cockle shells are a natural reservoir of calcium carbonate (CaCO3), which is widely used in bone repair, tissue scaffolds, and the development of advanced drug delivery systems. Although many studies report on the preparation of CaCO3, the development of a nanosized spherical CaCO3 precursor for calcium oxide (CaO) that is suitable to be incorporated in dental material was scarce. Therefore, this study aimed to synthesize a nanosized spherical CaCO3 precursor for CaO derived from cockle shells using a sol–gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Some of the popular method for synthesizing calcium carbonate nanoparticles viz. precipitation [ 43 ], sol-gel method [ 52 , 53 ], and layer by layer deposition [ 51 ]. As explained by the name, the top-down method is where larger particles (blood cockle shells) are broken down into smaller nanometer-sized particles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the popular method for synthesizing calcium carbonate nanoparticles viz. precipitation [ 43 ], sol-gel method [ 52 , 53 ], and layer by layer deposition [ 51 ]. As explained by the name, the top-down method is where larger particles (blood cockle shells) are broken down into smaller nanometer-sized particles.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies by Yang et al [ 94 ] and Chong et al [ 95 ] revealed that there occurs a strong peak at 2θ of 29.4, indicative of calcite, and this peak disappeared when the calcium carbonate became aragonite. In a paper published by Hussein et al [ 53 ] where the cockle shells were used to synthesize nanoparticles using a sol-gel method, this resulted in a calcite phase, characterized by the peak of 2θ at 29.5, was the confirmatory sign of calcite. In the current study, we found no diffraction around that region in the diffractogram of the nanoparticles synthesized, which indicates that these nanoparticles are purely aragonite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported, Ce-TZP/A is currently the toughest zirconia material available, and its fracture toughness reaches 19 MPa m 1/2 , and the flexural strength is high as 1400 MPa [65]. More importantly, Ce-TZP/A is entirely resistant to low-temperature aging degradation (LTAD), a critical drawback of Y-TZP [67]. The tremendous improvement of these characteristics is expected to extend the clinical application of dental ceramics to all-ceramic restorations and other areas, such as implant abutments, implants, removable denture bases, and components.…”
Section: Ceramicmentioning
confidence: 95%